Implementation of the Boarding School Program in the Formation of Religious Character of Students at Insan Madani Jambi Junior High School - Ziadatul Hilmi; Dewi Hasanah (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to describe the implementation of the boarding school program in forming the religious character of students at SMP Insan Madani Jambi, to identify its supporting and inhibiting factors, and to analyze the forms of religious character developed through the program. This research employed a descriptive qualitative approach. Data were collected through in-depth interviews, observation, and documentation involving the school principal, dormitory supervisors, Islamic Religious Education teachers, and students. Data validity was ensured through source and technique triangulation. The results show that the boarding school program is implemented through a structured 24-hour habituation system, including daily worship practices such as congregational prayers, Qur’an recitation, Qiyamul Lail, Dhuha prayer, and character guidance through role modeling and continuous supervision. Supporting factors include a strong institutional vision, a conducive dormitory environment, comprehensive religious programs, and active involvement of educators. Meanwhile, inhibiting factors consist of limited human resources, students’ adaptation challenges, homesickness, and fatigue due to dense routines. The religious character formed includes discipline in worship, obedience, respect for teachers, self-control, honesty, responsibility, and social awareness based on Islamic values. It can be concluded that the boarding school program is effective in shaping students’ religious character, although improvements in human resources and program innovation are still needed to optimize the internalization of values.